White grapes arose through the mutation of two similar and adjacent regulatory genes - Walker, Amanda R.; Bogs, Jochen (The plant journal, 2007)
Most of the thousands of grapevine cultivars (Vitis vinifera L.) can be divided into two groups, red and white, based on the presence or absence of anthocyanin in the berry skin, which has been found from genetic experiments to be controlled by a single locus. A regulatory gene, VvMYBA1, which could activate anthocyanin biosynthesis in a transient assay, was recently shown not to be transcribed in white berries due to the presence of a retrotransposon in the promoter. We have found that the berry colour locus comprises two very similar genes, VvMYBA1 and VvMYBA2, located on a single bacterial artificial chromosome. Either gene can regulate colour in the grape berry. The white berry allele of VvMYBA2 is inactivated by two non-conservative mutations, one leads to an amino acid substitution and the other to a frame shift resulting in a smaller protein. Transient assays showed that either mutation removed the ability of the regulator to switch on anthocyanin biosynthesis. VvMYBA2 sequence analyses, together with marker information, confirmed that 55 white cultivars all contain the white berry allele, but not red berry alleles. These results suggest that all extant white cultivars of grape vines have a common origin. We conclude that rare mutational events occurring in two adjacent genes were essential for the genesis of the white grapes used to produce the white wines and white table grapes we enjoy today.